PSYCHIC CRISIS CARE DURING THE COVID-19 PANDEMIC IN THE LIGHT OF NECROPOLITICS - Wünsch, Carla Gabriela; Kantorski, Luciane Prado (Cogitare Enfermagem, 2024)
Objective: to analyze care in severe psychic crises from the perspective of health professionals, people, and family members during the COVID-19 pandemic. Method: a multiple-case study, carried out with eight health professionals, six people in a crisis, and seven family members, monitored for three months, from October 2021 to June 2022, in a Brazilian capital. The data was analyzed using content analysis and the theoretical framework of necropolitics. Results: three categories emerged: "Scrapping the Psychosocial Care Network," "Outpatient Psychosocial Care Centre," and "Attending to the psychic crisis in the pandemic." This confirms a necropolitics that cuts across the field of mental health and affects vulnerable people, and the debate on funding and race is urgent. Conclusion: The lack of specialized mental health services, coupled with outpatient mental health services that began before the pandemic, has worsened crisis care.